2009
DOI: 10.1021/es902347z
|View full text |Cite
|
Sign up to set email alerts
|

Peruvian Gold Rush Threatens Health and the Environment

Abstract: recalls when his neighbor's nine-year-old son accidentally drank mercury from a bottle he found in the family's home. When the boy died two years later, his parents separated, his mother blaming her husband for not keeping the bottle out of their son's reach. It is a cautionary tale in Madre de Dios, a region in southeastern Peru where smallscale, "artisanal" gold miners like Miranda and his neighbor use mercury every day, with little or no equipment to protect themselves against skin contact or inhalation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…Considering ongoing threats in the region from infrastructure development [88], oil extraction [89], gold mining [90,91], illicit crops [36], and the continually advancing agricultural fronts, more carefully situated protected areas and novel land use regulation strategies will be necessary to safeguard substantial amounts of biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…Considering ongoing threats in the region from infrastructure development [88], oil extraction [89], gold mining [90,91], illicit crops [36], and the continually advancing agricultural fronts, more carefully situated protected areas and novel land use regulation strategies will be necessary to safeguard substantial amounts of biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…The environmental and health problems caused by mercury are well documented [13], yet its use continues to be an intrinsic component in today's artisanal mining [8], [14]. Artisanal miners are directly exposed to liquid mercury as well as to vapors during gold processing, which releases mercury directly into sediments, waterways and the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found elevated mercury exposure among residents of artisanal mining communities throughout Asia [6,7], Africa [8,9], and South America [10][11][12][13][14][15][16][17]. The Peruvian Amazon is a growing hotbed for artisanal mining, and there is growing concern over the extensive environmental mercury contamination that is occurring here [18][19][20]. One region in particular-Madre de Dios-is estimated to house approximately 30,000 artisanal miners [18].…”
Section: Introductionmentioning
confidence: 99%
“…The Peruvian Amazon is a growing hotbed for artisanal mining, and there is growing concern over the extensive environmental mercury contamination that is occurring here [18][19][20]. One region in particular-Madre de Dios-is estimated to house approximately 30,000 artisanal miners [18]. However, many studies from this region have important laboratory limitations, with many not calculating creatinine-corrected urine mercury concentrations, and most not assessing blood methylmercury.…”
Section: Introductionmentioning
confidence: 99%